제왕절개술에서 전신마취시와 lidocaine 또는 lidocaine-fentanyl 을 이용한 경막외마취시의 술후 통증 비교 - 지대림; Dae Lim Jee; 신건; Keon Shin; 한석주; Seok Ju Han; 김세연; Se Yeon Kim; 박노천; No Cheon Park; 박대팔; Dae Pal Park; et al. (Korean journal of anesthesiology, 1997)
Background : A recent report suggested that intrathecal local anesthetic pretreatment alone might not be beneficial for the prevention of postoperative pain possibly due to a increase in spinal excitability. We tested that the effect of centrineuraxis block would be more effective on postoperative pain than general anesthesia and lidocaine-fentanyl epidural block would reduce pain more effectively than lidocaine epidural. Methods : Parturient patients scheduled for cesarean section were randomly assigned to receive single epidural block using lidocaine alone(Group LE, n = 15), or with fentanyl(Group LFE, n = 15) to T4 or more sensory level, and enflurane anesthesia(Group G, n = 15). To relieve postoperative pain, all patients received intravenous bolus morphine on pain, followed by the intravenous patient-controlled analgesia(IV-PCA). Visual analogue scores(VAS) and cumulative morphine consumptions were measured at time intervals. Comparisons were made within and between groups. Results : VAS and morphine consumption for first 24 hours were less in Group LE and LFE than in Group G over the time interval without difference between Group LE and LFE(P＜0.05). The morphine consumptions in Group LE(1.07±0.80 mg) and LFE(1.00±0.93 mg) were lower than in Group G(2.40±0.83 mg) at 24 hour(P＜0.05). There were no differences between 3 groups in 24 hours' morphine consumption during the second day. Conclusions : Epidural block is more effective than general anesthesia on pain relief. Lidocaine- fentanyl epidurals are not more effective than lidocaine alone on postoperative pain relief, suggesting no significant effect on spinal sensitization of fentanyl. IV-PCA in patients with epidural block can be stopped earlier than with general anesthesia postoperatively. (Korean J Anesthesiol 1997; 33: 697∼703)